2020
DOI: 10.1002/advs.202002273
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Orphan Receptor NR2F6 Promotes Hepatic Steatosis through Upregulation of Fatty Acid Transporter CD36

Abstract: Nuclear receptors (NRs) are a superfamily of transcription factors which sense hormonal signals or nutrients to regulate various biological events, including development, reproduction, and metabolism. Here, this study identifies nuclear receptor subfamily 2, group F, member 6 (NR2F6), as an important regulator of hepatic triglyceride (TG) homeostasis and causal factor in the development of non‐alcoholic fatty liver disease (NAFLD). Adeno‐associated virus (AAV)‐mediated overexpression of NR2F6 in the liver prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 60 publications
1
32
0
1
Order By: Relevance
“…CD36 is one of the best characterized mediators that promote the transport of fatty acids into cells. Abundant studies have demonstrated that the expression of hepatic CD36 is increased during the development of NAFLD with the capability of promoting hepatic fatty acids uptake, thus resulting in the enhancement of hepatic steatosis (Steneberg et al, 2015;Zhou et al, 2020). Consistent with previous reports, our study has shown increased mRNA expression of hepatic ACC1 and CD36 in MCD-induced NASH mice.…”
Section: Discussionsupporting
confidence: 92%
“…CD36 is one of the best characterized mediators that promote the transport of fatty acids into cells. Abundant studies have demonstrated that the expression of hepatic CD36 is increased during the development of NAFLD with the capability of promoting hepatic fatty acids uptake, thus resulting in the enhancement of hepatic steatosis (Steneberg et al, 2015;Zhou et al, 2020). Consistent with previous reports, our study has shown increased mRNA expression of hepatic ACC1 and CD36 in MCD-induced NASH mice.…”
Section: Discussionsupporting
confidence: 92%
“…Novel HNF4α, FOXA1, and CEBPα binding motifs were found to be enriched at the unique responsive regulatory elements in rhesus macaques, as well as motifs for other TFs such as JUN and NR2F6 (Fig. 2e) that have been shown to be essential for the regulation of metabolism in the liver [42,43]. At loci with partial sequence conservation, these novel TFs binding motifs can be the result of sequence mutations in TF recognition sequences driving the divergence of regulatory element response between species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the observed NR2F6 upregulation in biopsies of patients with defined cancer entities [ 39 , 45 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 ] ( Figure 1 and Table 1 ) might thus implicate an upregulation also of lymphatic NR2F6. This, however, still needs to be evaluated for patient stratification purposes.…”
Section: Beyond Current Immune Checkpoint Therapiesmentioning
confidence: 98%
“…Remarkably, beside its role in immune cells, NR2F6 expression also appears important in tumor cells, correlating with a faster tumor growth and worse patient overall survival outcomes ( Table 1 ). Human studies firmly established an increased NR2F6 expression in various cancer types such as leukemia [ 41 , 56 ], colon carcinoma [ 39 ], cervical cancer [ 42 ], ovarian cancer [ 43 , 44 ], breast cancer [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], lung cancer [ 45 , 58 ] and hepatocellular cancer [ 38 ], suggesting that NR2F6 might be a prognostic marker. NR2F6 might directly regulate and elevate the survivability of cancerous colon cells via XIAP (X-Linked Inhibitor of Apoptosis) [ 39 ], whereas it supports proliferation and metastasis in hepatocellular carcinoma via TIP60 regulation [ 38 ], which is already known to promote mammary tumorigenesis [ 58 ], pleural mesothelioma malignancy [ 59 ] and prostate cancer [ 60 ] growth.…”
Section: Beyond Current Immune Checkpoint Therapiesmentioning
confidence: 99%